Educational pathfinders? A study of international student mobility in China - Lee, KH (2021)
To date, a significant body of qualitative scholarship on international student mobility has centred around migration flows to ‘Western’ destinations, particularly to Anglophone and/or European nations. On the contrary, educational migration from these established destination regions to newly emerging study abroad destinations is a relatively recent phenomenon and, consequently, remains eminently under-researched. To fill this gap in our knowledge, I discuss the findings of a qualitative study into European and North American students undertaking an English-taught undergraduate degree in China. Using literature from human geography, sociology, education, migration studies and tourism studies, this thesis explores the ways in which ‘Western’ transnational students engage with, and make meaning of, cross-border mobility, transnational higher education, and cosmopolitanism in neoliberal times.